Effect of Packaging Materials and Storage Time on Anthocyanins Stability of Red Cabbage-Roselle Mixed Drink - Muhamad, N.F.H.; Hussin, F.; Norlelawati Arifin (Rynnye Lyan Resources, 2024)
This study aimed to investigate the effect of different packaging materials on anthocyanins' stability of red cabbage-roselle mixed drink during 6-month storage. The mixed drink was pasteurised and hot-filled into three different packaging materials, i.e., transparent glass bottle, beverage metal can, and polypropylene (PP) bottle, then stored at ambient temperature (29±2°C). During storage, packaging materials and storage time significantly affect the anthocyanin content, colour density, and polymeric colour percentage of red cabbage-roselle mixed drink packed in a glass bottle, can, and PP bottle. Polymeric colour percentage and degradation index of red cabbage-roselle mixed drink were found to increase significantly during storage at the ambient temperature, whereas total anthocyanin content and colour density decreased significantly irrespective of packaging materials used. The correlation analysis reveals that total anthocyanin content has a significant positive correlation with colour density but negatively correlates with polymeric colour percentage and degradation index regardless of packaging materials used. The total anthocyanin content decreases significantly irrespective of the packaging materials used. The mixed drink in glass bottles significantly (p<0.05) has the highest retention of anthocyanins content, followed by mixed drinks stored in cans and PP bottles. Therefore, glass bottles should be chosen as the most suitable packaging material to store the mixed drink, followed by cans and PP bottles as glass bottles provide better stability of anthocyanins for a red cabbage-roselle mixed drink